OUTCOME OF ANTIFUNGAL COMBINATION THERAPY FOR INVASIVE MOLD INFECTIONS IN HEMATOLOGICAL PATIENTS IS INDEPENDENT OF THE CHOSEN COMBINATION - Rafael Rojas; José R. Molina; Isidro Jarque; Miguel A. Sanz (Mediterranean Journal of Hematology and Infectious Diseases, 2012)
Invasive mold infection (IMI) remains a major cause of mortality in high-risk hematological patients. The aim of this multicenter retrospective, observational study was to evaluate antifungal combination therapy for proven and probable IMI in hematological patients. We analyzed 61 consecutive cases of proven (n=25) and probable (n=36) IMI treated with antifungal combination therapy (ACT) collected from eight Spanish hospitals from January 2005 to December 2009. Causal pathogens were: Aspergillus spp (n=49), Zygomycetes (n=6), Fusarium spp (n=3), and Scedosporium spp (n=3). Patients were classified in three groups according to the antifungal combination employed: Group A, liposomal amphotericin B (L-Amb) plus caspofungin (n=20); Group B, L-Amb plus a triazole (n=20), and Group C, voriconazole plus a candin (n=21). ACT was well tolerated with minimal adverse effects. Thirty-eight patients (62.3%) achieved a favorable response (35 complete). End of treatment and 12-week survival rates were 62.3% and 57.4% respectively, without statistical differences among groups. Granulocyte recovery was significantly related to favorable responses and survival (p<0.001) in multivariate analysis. Our results suggest that comparable outcomes can be achieved with ACT in high risk hematological patients with proven or probable IMI, whatever the combination of antifungal agents used.